(3TQM HOjYjI GHf MLI GdMehis - (3CHh HcQ Hf Ydj Hf YHO Gddg GdMehj GdCRQGQj, Jbj GdOjf GHf MLI,J (B837 (3g` s ((3eMeO Hf JZQi HOi GdSjai ShOhf HbLI Gdedci GdCTQai s)
(3ChdgG (B:s
(3hHYO agPg GdHOjYjI GdJi fSLJgG HeOMg (B((3U(B) (3Ydi efhGd WQM GdHQOI heGPGc EdG Gfg hba HOeTb GdeMQhSI Ydi bUjOI HOjYjI s
(3BNQgG (B:s
(3eSJWQOkG Edi ESJjYGH eGh bY ef LjOg hQOjI hChQOJ ai MSf GJNdU eG hbY ef HOjYI hZQjHI s
(3TQM HOjYjI ddeDda ai (B143 (3HjJkG SeGgG CHj HcQs
(3hHBNQ UaMGJgG JYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdJGSYs
(3JHUQI GdYfhGf (B:s
(3TQMs
Keywords: (3GdCOHs